Analysis of Turmeric Commodity Development in Improving Farmers' Welfare from a Sharia Economic Perspective (Case Study of Riamau Village, Bima Regency) - Nurmelisah Nurmelisah; Rafiuddin Rafiuddin; Ibrahim Ibrahim (JURNAL ECONOMINA, 2026)
This study aims to analyze the development of turmeric commodities in improving farmers’ welfare from the perspective of Islamic economics in Riamau Village, Bima Regency. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews, observations, and documentation involving 10 turmeric farmers in Riamau Village. The results of the study show that turmeric farmers in Riamau Village still sell their harvests directly to the market without intermediaries or middlemen. The selling price of turmeric ranges from IDR 30,000 per 10 kilograms, with the product sold in raw form. Turmeric production is still conducted traditionally, and the average harvest income only reaches around IDR 300,000 – 500,000 per harvest each year. This income has not been sufficient to meet daily living needs because turmeric farming is only considered an additional source of income. In addition, farmers have only received training once and still face unstable market prices. From the perspective of Islamic economics, turmeric farming practices in Riamau Village reflect the principles of honesty and transparency in transactions. However, these practices have not been optimal in realizing the welfare and public benefit (maslahah) of farmers. Therefore, government support, stronger marketing strategies, continuous training, and turmeric product processing are needed to create higher economic added value.